Corrigendum: Influence of metal matrix powder size on the tensile strength of a SiCp/AlSi7Mg0, 6 composite produced by field assisted sintering technique (2021 IOP Conf. Ser.: Mater Sci Eng. 1147 012020). Issue 1 (May 2021) - Pippig, R; Hirsch, S J; Grund, T; Lampke, T
Abstract : In the section Results and Discussion of our published paper the units for the heating energy and the toughness contain a mistake.